2016
DOI: 10.1007/s00029-016-0257-7
|View full text |Cite
|
Sign up to set email alerts
|

The big projective module as a nearby cycles sheaf

Abstract: We give a new geometric construction of the big projective module in the principal block of the BGG category O, or rather the corresponding D-module on the flag variety. Namely, given a one-parameter family of nondegenerate additive characters of the unipotent radical of a Borel subgroup which degenerate to the trivial character, there is a corresponding one-parameter family of Whittaker sheaves. We show that the unipotent nearby cycles functor applied to this family yields the big projective D-module.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…This generalizes some known relations between Whittaker and tilting/projective modules in the classic BGG category O [81][82][83]. For abelian theories, the conjecture is proven in [84].…”
Section: Jhep10(2016)108supporting
confidence: 65%
See 1 more Smart Citation
“…This generalizes some known relations between Whittaker and tilting/projective modules in the classic BGG category O [81][82][83]. For abelian theories, the conjecture is proven in [84].…”
Section: Jhep10(2016)108supporting
confidence: 65%
“…In particular, all projective and tilting modules in O C arise this way. In geometric representation theory, it is known that a non-degenerate Whittaker module over a semisimple Lie algebra can be averaged or degenerated to give the "big" projective module in the BGG category O [81][82][83]. Our analysis of Neumann b.c.…”
Section: Jhep10(2016)108mentioning
confidence: 99%
“…The canonical map is given in these terms by . It follows from [Cam17, Example 4.3] that is the cohomologically normalized pullback of the unique indecomposable tilting sheaf on which extends . Moreover, the monodromy filtration satisfies , , and , where .…”
Section: First Proof Of Theorem 141mentioning
confidence: 99%
“…In [Cam17], the author introduced a similar construction in the situation of a finite-dimensional flag variety. Namely, we showed that the nearby cycles of a one-parameter family of nondegenerate Whittaker sheaves on a flag variety is the big projective sheaf, which is isomorphic to the tilting extension of the constant perverse sheaf on the big cell.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several constructions of tilting objects as sheaves or D-modules, including certain averaging or limiting process (c.f. [7], [14], [3], [5]). In this paper, we construct the tilting object corresponding to the open Schubert cell, often referred as the big tilting, as a holomorphic Lagrangian brane in the Fukaya category F (T * B).…”
Section: Introductionmentioning
confidence: 99%